CAUSES AND DISTRIBUTION FEATURES OF FORESTIN ALDER STANDS (ALNUS GLUTINOSA (L.) GAERTH.) IN UKRAINE FOR THE PERIOD OF 1991–2009 - Ustskiy, I. M.; Bugaev, S. M.; Nykytyuk, P. A. (Forestry and Forest Melioration, 2018)
Introduction Secondary growth coppice stands formed mainly at the site of alder stands of seedling origin in Ukraine. Such stands have simplified structure, reduced stability and production. The spreading of pathological processes in alder stands are caused by anthropogenic impacts and climate changes. Climatic changes of recent years lead generally to increased number of negative factors that cause drying-out of alder stands, the nature and intensity of which should be the subject of investigation. The aim of our study is to establish the causes of deterioration in sanitary conditions of alder stands and to identify specific inventory characteristics of alder stands covered by various pathological processes. Methods of research Research conducted by sample surveys using conventional methods in forestry, analyzing and collating of subcompartment database collected using the method of URIFFM as on 2004, 2007, 2000, 2003, 2006 and 2009 years. Results The survey results suggest that pathological processes observed in alder stands of all age classes, but the most of plantations (30 % of the area) were of 6th age class. The part of 5th and 7th age classes of the stands was somewhat smaller (21 % and 18 %, respectively). Area of plantation, weakened and dried due to various reasons, varies depending on the period of examination, but the ratio of classes of initiating causes remains relatively stable; they are changes the hydrological regime and related diseases (60 % and 20 % respectively), the impact of drought, frost, wind throw, wind-breakage (10 %), fire damage (2 %), negative human impact (industrial emissions, cutting, etc.) (3 %), other reasons, including not defined, account for about 5 % of all weakened and drying stands. In terms of regional departments as on 2009, the largest area of alder trees weakened due to the changes of the hydrological regime were marked in the Poltava and Volyn Regional Departments of Forestry and Hunting (43.2 % and 36.3 %, respectively). The largest areas of alder stands affected by stem rot were registered in Kiev Regional Department of Forestry and Hunting (82 % of all alder stands, drying due to this reason in Ukraine). Stands distribution by the stand density shows that more than 80 % of the areas of plantations marked with pathological processes have stand density accounted for 0.6–0.8, and more than a half of them (42 %) have 0.7. The ratio of alder drying stands of the second site class prevailed in all periods, and only as on1994 most drying alder stands were of the first site class. Conclusions The main reasons for initiating the degradation of alder stands in Ukraine for the period of 1994–2009 are hydrological regime changing and disease (stem rot). The spreading of pathological processes depends on the period of examinations and observed mainly in the stands of 6th age class, of second site class and of middle and lower stand density. As of 2009, the largest area of alder trees weakened due to the changes of the hydrological regime were marked in the Poltava and Volyn Regional Department of Forestry and Hunting, and in connection with damage by stem rot the largest area was registered in Kiev Regional Department of Forestry and Hunting.